Effects of electronic voice intensity monitoring on hard glottal attack - Sansone Jr., F.E. (IRCS Medical Science, 1982)
An electronic device capable of monitoring the rate at which voice intensity increases during voice onset provides an indicator of the abruptness of phonatory initiation. Two groups of 8 subjects were taught to reduce the abruptness of glottal attack. Group A used a seven step program employing the electronic monitor while Group B used the same seven step program but with a traditional approach to the reduction of abrupt glottal attack substituted for monitor use. Both groups used a self-instruct teaching paradigm. Subject recordings of pre and post program production of five voice onset moments were submitted to sonographic amplitude analysis and a time/intensity slope ratio was calculated for each. Further, the pre and post program recordings were judged for abruptness of glottal attack. Post program slope ratios and attack judgments were significantly different (p < 0.01) from pre program data for Group A only. These data suggest that electronic monitoring was effective in producing gradual phonatory initiation.
Keywords: central nervous system; dept.cmd; glottis spasm; human cell; larynx; normal human; phonation; voice; ⛔ No DOI found